PENGEMBANGAN MESIN PEMISAH KULIT POLONG KACANG HIJAU UNTUK PENINGKATAN KAPASITAS DAN EFISIENSI PEMISAHAN BIJI - Ahmad Nurul Muttaqin; Uswatul Hasanah Mihdar; Arfandy Arfandy (Machine : Jurnal Teknik Mesin, 2023)
The objective of this study is to improve the quality and efficiency of the verification process which is crucial for processing green bean seeds by upgrading the green bean skin separating machine. This change entails improving engine rotation in addition to changing engine mechanics and parts. The engine was tested at 350 rpm, 425 rpm, and 500 rpm during the experimental phase. According to the data, 350 rpm is the ideal engine speed for separating green bean seeds from the pod skin, with a differential capacity of 54 kg/hour. When ninety percent of the green bean seeds are undamaged and out of the pod skin, they are combined with other components. This machine may serve as a commercial solution to improve the quality and efficiency of processing green bean seeds. These encouraging outcomes highlight how important technology is to the agro-industrial and agricultural sectors. By processing green bean seeds more effectively and of higher quality, technology may also assist the environment and the economy.